Controlling the Microstructure of Conjugated Polymers in High‐Mobility Monolayer Transistors via the Dissolution Temperature. Issue 2 (20th November 2019) - Li, Mengmeng; Bin, Haijun; Jiao, Xuechen; Wienk, Martijn M.; Yan, He; Janssen, René A. J.
Abstract: It remains a challenge to precisely tailor the morphology of polymer monolayers to control charge transport. Herein, the effect of the dissolution temperature ( T dis ) is investigated as a powerful strategy for morphology control. Low T dis values cause extended polymer aggregation in solution and induce larger nanofibrils in a monolayer network with more pronounced π–π stacking. The field‐effect mobility of the corresponding monolayer transistors is significantly enhanced by a factor of four compared to devices obtained from high T dis with a value approaching 1 cm 2  V −1  s −1 . Besides that, the solution kinetics reveal a higher growth rate of aggregates at low T dis, and filtration experiments further confirm that the dependence of the fibril width in monolayers on T dis is consistent with the aggregate size in solution. The generalizability of the T dis effect on polymer aggregation is demonstrated using three other conjugated polymer systems. These results open new avenues for the precise control of polymer aggregation for high‐mobility monolayer transistors. Abstract : Cool down ! The dissolution temperature is an efficient parameter to control the aggregation of conjugated polymers in solution and to influence their microstructure in monolayers. A lower dissolution temperature induces stronger π–π stacking interactions and larger fibrillar domains, resulting in high‐performance monolayer transistors with a mobility approaching 1 cm 2  V −1  s −1 .